2022
DOI: 10.1002/psp.2559
|View full text |Cite
|
Sign up to set email alerts
|

From rural exodus to repopulation in Mexico's Mixteca Alta? Analyzing differential trends

Abstract: This paper analyzes differential trends in rural depopulation and repopulation in nine municipalities of Mexico's Mixteca Alta region, in the southern state of Oaxaca, based on census data and interviews carried out in 2019. From 1950 to 2000, the study area experienced a substantial loss of population, linked essentially to out‐migration to Mexico City. However, from 2000 to 2020, four of the municipalities regained population, while the remaining five continued losing residents. This repopulation is explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…However, as opposed to Yanhuitlán, only 4.2 percent of minors lived with their mothers but not with their fathers. Nevertheless, out-migration is also significant in this municipality (Lorenzen, 2021; 2022) and is reflected in the age structure of the population, 20.8 percent being 65 years or older (even more than in Yanhuitlán), 48.8 percent 20 to 64, and 30.4 percent under 20. Lastly, 53.2 percent of the population was made up of women (INEGI, 2020).…”
Section: The Study Areamentioning
confidence: 91%
See 1 more Smart Citation
“…However, as opposed to Yanhuitlán, only 4.2 percent of minors lived with their mothers but not with their fathers. Nevertheless, out-migration is also significant in this municipality (Lorenzen, 2021; 2022) and is reflected in the age structure of the population, 20.8 percent being 65 years or older (even more than in Yanhuitlán), 48.8 percent 20 to 64, and 30.4 percent under 20. Lastly, 53.2 percent of the population was made up of women (INEGI, 2020).…”
Section: The Study Areamentioning
confidence: 91%
“…This paper is essentially based on semistructured, open-ended interviews with key informants from Tonaltepec and Yanhuitlán. We have carried out fieldwork in these municipalities since 2018, addressing issues such as natural resource management, changes in agriculture, socioeconomic changes, and migration (e.g., Lorenzen, 2021; 2022; Lorenzen et al, 2020; 2021; Orozco-Ramírez and Bocco, 2021; Orozco-Ramírez, Bocco, and Solís-Castillo, 2020). This has allowed us to establish close relationships with various residents, including a group of local geopark guides.…”
Section: Methodsmentioning
confidence: 99%
“…Entre las consecuencias de tales problemáticas, cabe destacar el incremento de la migración del campo a la ciudad de población mayormente joven y de sexo femenino, en búsqueda de mejores condiciones de educación, trabajo y servicios básicos, provocando envejecimiento y masculinización de las zonas rurales (Rodríguez et al, 2016). Otros trabajos mencionan el abandono progresivo de la tierra y la insustentabilidad de los territorios (Hori et al, 2021), así como cambios en la dinámica espacial de los asentamientos y en las prácticas económicas de sustento (Lorenzen, 2022).…”
Section: Estudios Del Despoblamiento Ruralunclassified
“…A 2019 study conducted in nine municipalities in Mexico's Mixteca Alta region in Oaxaca state, found that between 1950 and 2000, there was a significant increase in population retention due to local tertiarization, the ability to commute to nearby small cities, and a decrease in traditional pull factors (Lorenzen, 2022). Moreover, economic deindustrialization has largely been driven by the transition from manufacturing to the service sector and the development of knowledge-based industries, which indirectly drive counterurbanization (Jimenez et al, 2021).…”
Section: Theoretical Foundationmentioning
confidence: 99%